Kontrastiva studier i nederländska och svenska Med en inledning om tredjespråksinlärning och tvärspråklig medvetenhet - Johansson, Annika (Stockholm German and Dutch Studies, 2019)
This book deals with two research fields and brings them together: contrastive linguistics and third language acquisition. The book describes the following linguistic structures in Dutch and Swedish from a contrastive perspective: spatial adverbs, copula, impersonal passives, impersonal constructions and finally the posture verbs stand, zit and lie. Dutch and Swedish are usually acquired as a third language and not as a second language, which implies that learners already comprehend various other languages. When learning a language these multilingual learners have developed certain strategies which draw on their competence in earlier studied languages. In the process of learning a third language, metalinguistic and cross-linguistic awareness play an important role. Comparing linguistic structures in two closely related languages as Dutch and Swedish can enhance cross-linguistic awareness and therefore be used as a didactic tool.